2015
DOI: 10.1163/15685403-00003501
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the parasite Probopyrus pandalicola (Packard, 1879) (Isopoda, Bopyridae) on the behavior, transparent camouflage, and predators of Palaemonetes pugio Holthuis, 1949 (Decapoda, Palaemonidae)

Abstract: The bopyrid isopod Probopyrus pandalicola (Packard, 1879) is a large, noticeable, hematophagous ectoparasite of palaemonid shrimps, including the daggerblade grass shrimp Palaemonetes pugio Holthuis, 1949. Bopyrids affect grass shrimp physiology and may also affect predator-prey dynamics. The purpose of this study was to determine whether the isopod affected the behavior and/or camouflage of grass shrimp, thereby altering the predation preferences of the mummichog Fundulus heteroclitus (Linnaeus, 1766). To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These authors concluded that the alterations were consistent with the ingestion of the branchial tissue by P. bithynis , which would have a negative impact on the respiratory capacity of the host. Infestation by Probopyrus females may also induce the castration of the host, the feminization of the males (Beck, 1980), reduction of the development of the nutritional conditions of the host (de Barros et al ., 2021), and even predator−prey interactions, through the reduction in the capacity of the host to camouflage itself, leaving it more susceptible to predation (Brinton and Curran, 2015 b ).…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that the alterations were consistent with the ingestion of the branchial tissue by P. bithynis , which would have a negative impact on the respiratory capacity of the host. Infestation by Probopyrus females may also induce the castration of the host, the feminization of the males (Beck, 1980), reduction of the development of the nutritional conditions of the host (de Barros et al ., 2021), and even predator−prey interactions, through the reduction in the capacity of the host to camouflage itself, leaving it more susceptible to predation (Brinton and Curran, 2015 b ).…”
Section: Introductionmentioning
confidence: 99%